2022
DOI: 10.3390/ijerph192315804
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Gestational Diabetes Mellitus across Continents in 21st Century

Abstract: Over the last few decades, several definitions of gestational diabetes mellitus (GDM) have been described. There is currently not enough research to show which way is the best to diagnose GDM. Opinions differ in terms of the optimal screening and diagnostic measures, in part due to the differences in the population risks, the cost-effectiveness considerations, and the lack of an evidence base to support large national screening programs. The basic method for identifying the disease is the measurement of glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 203 publications
1
4
0
Order By: Relevance
“…The incidence of GDM in our population is consistent with previous European studies [ 27 , 28 ]. In addition, a recent meta-analysis indicated that the overall weighted prevalence of GDM in a total of 24 European countries was 10.9% [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of GDM in our population is consistent with previous European studies [ 27 , 28 ]. In addition, a recent meta-analysis indicated that the overall weighted prevalence of GDM in a total of 24 European countries was 10.9% [ 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…Currently, the traditional model is used for diagnosing GDM. Screening tests may vary slightly depending on the health care provider but generally include: initial glucose challenge test, where a blood sugar level of 190 milligrams per deciliter (mg/dL) or 10.6 millimoles per liter (mmol/L) indicates gestational diabetes [31,32]. A blood sugar level below 140 mg/dL (7.8 mmol/L) is usually considered within the standard range on a glucose challenge test, although this may vary by clinic or lab.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a large amount of literature has confirmed that insulin aspart treatment can greatly reduce nesfatin-1, CTRP12, and blood glucose levels. [31,32] Another study found that the incidence of adverse pregnancy and perinatal outcomes in patients with GDM is greatly reduced by dietary interventions and insulin aspart treatment. [33] The results of this study showed that, after treatment, the proportion of adverse pregnancy outcomes in the observation group was significantly lower than that in the control group, and the proportions of premature infants, macrosomia, fetal distress, neonatal asphyxia, and neonatal hypoglycemia in the observation group were significantly lower than those in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a large amount of literature has confirmed that insulin aspart treatment can greatly reduce nesfatin-1, CTRP12, and blood glucose levels. [ 31 , 32 ]…”
Section: Discussionmentioning
confidence: 99%